Antinociceptive Analysis of Natural Monoterpenes Eugenol, Menthol, Carvacrol and Thymol in a Zebrafish Larval Model - Cláudia Alexandra Rocha; Luís M. Félix; Sandra Mariza Monteiro; Carlos Venâncio (MDPI AG, 2024)
In the last decade, a considerable number of studies have broadened our knowledge of the nociceptive mechanisms of pain, a global health problem in both humans and animals. The use of herbal compounds such as eugenol, menthol, thymol, and carvacrol as analgesic agents has accompanied the growing interest in this area, offering a possible solution for this complex problem. Here, we aimed to explore how these natural substances-at three different concentrations (2, 5 and 10 mg/L)-affect the pain responses in zebrafish (Danio rerio) larvae exposed to 0.05% acetic acid (AA) for 1 min. By analysing the activity of acetylcholinesterase (AChE), 5'-ectonucleotidase and NTPDases, as well as aversion and exploratory behaviours, it was observed that that although all substances were effective in counteracting the pain stimulus, the concentration range within which they do so might be very limited. Eugenol, despite its acknowledged properties in fish anaesthesia, failed to alleviate the pain stimulus at low concentrations. Contrastingly, menthol exhibited the most promising results at the lowest concentrations tested. Overall, it is concluded that menthol might be a good analgesic for this species, qualifying it as a substance of interest for prospective studies.